Callus molding in external and internal distraction of mandible - S M Balaji (Wolters Kluwer Medknow Publications, 2015)
Background: Distraction osteogenesis (DO) emerges to be a promising alternative to the traditional method of bone lengthening, by which a significant skeletal and soft tissue enlargement can be obtained in the hypoplastic area in a short period. Manipulations of the newly created callus (regenerate), during DO or as a single step molding procedure at the end of the distraction process, may be necessary to correct the mandibular position. Aim: To report the efficacy of callus molding (CM) - floating bone concept in the vertical lengthening of ramus by DO and creating a gonial angle in the difficult case of vector selection or surgically induced asymmetry. Materials and Methods: Retrospective analysis of patients who underwent DO of mandible followed by CM for correction of mandibular asymmetry at authors centers from 2008 to 2014 formed the study group. Only the mandibular distraction cases were included in the study. After the 5 days of latency period, the mandible was distracted at the rate of 1 mm/day. At the end of DO, CM was completed in the 1-3 weeks before consolidation. CM was done either by removing the lower screws with distractor in place or after removal of distractor based on case selection. Secondary maxillary correction by Le Fort I osteotomy using bone graft and further occlusion is corrected by postorthodontics if necessary. Splints were used during CM for predetermined occlusion. In all the cases, postoperative intermaxillary fixation was maintained for 8 weeks for stable ossification of the callus. Results: The study group consist of four and five cases of external and internal distraction, respectively. Of the 9 patients who underwent DO, 6 were females and 3 were males. The mean age of the population ranged from 10 to 21 years with a mean age of 18 years. The average distracted length of the mandible was 23.55 mm ranging from 20 to 26 mm with the standard deviation of 1.95. The mean deviation of the mandible (crossbite) at the end of distraction was around 8.23 mm ranging from 5 to 12 mm with the standard deviation of 2.17. Of the total 9 cases, only in 3 cases CM is done during DO and the rest 6 cases the CM is done after removal of the distractor. Secondary maxillary correction by Le Fort I osteotomy was done for 4 cases, and postorthodontic correction was done in 3 cases. In all the 9 cases, 100% results (as assessed clinically and radiographically) achieved with the creation of perfect gonial angle. Conclusions: CM plays a crucial role in those cases where proper vector orientation is hindered because of anatomical difficulty for osteotomy cuts and parallel fixation of the distractor to ramus resulting in cross-bite with deviation toward the undistracted side. Manipulation of the regenerates would provide a precise achievement of gonial angle, minimizing the need for secondary corrections, and diminishing treatment duration and costs.